EVALUASI KEBIJAKAN PROGRAM NASIONAL PEMBERDAYAAN MASYARAKAT MANDIRI PEDESAAN DI KELURAHAN KABONGA BESAR KECAMATAN BANAWA KABUPATEN DONGGALA - Haedar, Haedar (Katalogis, 2015)
This research aims at describing, analyzing and interpreting the evaluation of the implementation of National Program for Community Empowerment in Kabonga Besar. This is a qualitative research with descriptive method and the data collection techniques are observations, interviews, and documentations. This research involved 6 informants taken purposively. This research used the model of William Dunn policy evaluation, and it is obtained that the result is not optimal, and the factors which affected, namely: 1)the aspect of effectiveness is not optimal, because there are still problems women's credit refund is not smooth, 2) the aspect of efficiency is good, because the funds disbursed can be utilized as much as possible for the needs of the community, 3) the aspect of adequacy is good, because the program provides benefits to the villagers, 4) the leveling aspect is good, because the program spread to all levels of society, 5) the aspect of responsiveness is good, where the beneficiaries are satisfied with the program existence 5) the aspect of accuracy is good, because the beneficiaries consider that the program is useful for them.